Textile UWB Antennas for Biomedical Applications - S.Bhavani; Shanmuganantham, T.; Mouni, N.; Sai, G. Jaydeep (IRO Journal on Sustainable Wireless Systems, 2022)
In recent years, there has been an increase in worry about the security of Wireless Body Area Network systems, particularly worn electronics such as military, entertainment, and medical devices. The ability to communicate wirelessly from or to the body via conformal and wearable antennas is a major characteristic of modern wearable electronics. In this work, circular ring and fractal antennas are designed using a wearable substrate of denim with a dielectric constant of 1.7. Design and simulations are carried out in the CST Microwave environment and different performance characteristics of the antenna are examined in free space and on body medical applications.
Keywords: CST; fractal antenna; ring shape; textile substrate; tumor detection.